Volatile metabolomic signature of bladder cancer cell lines based on gas chromatography–mass spectrometry - Rodrigues, Daniela (2021)
Recent studies provide a convincing support that the presence of cancer cells in the body leads to the alteration of volatile organic compounds (VOCs) emanating from biological samples, particularly of those closely related with tumoral tissues. Thus, a great interest emerged for the study of cancer volatilome and subsequent attempts to confirm VOCs as potential diagnostic biomarkers.